Media Potbangtar Meningkatkan Hasil Belajar Menghitung Luas Bangun Datar pada Siswa Sekolah Dasar - Istafada, Istafada (Jurnal Didaktika Pendidikan Dasar, 2021)
Lack of understanding mathematical concepts that students accept will lead to low student learning outcomes. Teachers as a learning resource are obliged to provide a creative learning environment for students in the classroom. One of the activities that must be carried out by the teacher is selecting and determining appropriate media for learning. The objective of this research to determine improved learning outcomes in calculating the area of flat shape using potbangtar media. This research uses two rounds of action research. Each round consists of 4 stages, namely design, activity, observation, reflection, and revision. The data obtained are in the form of evaluation test results, observation sheets of teaching and learning activities. From the results of data analysis found that student learning outcomes increased from cycle I to cycle II, from 75.61 to 80.49 and student learning completeness also increased from cycle I (85.37%) to cycle II to (95.12%) ). We can conclude that the usage of potbangtar media to calculate the area of the flat shape is very effective so that the learning outcomes of the fifth-grade students of SDN MIJI 4, Mojokerto increase.